2012
DOI: 10.3724/sp.j.1037.2011.00533
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF PRE-DEFORMATION ON GRAINS AND PRECIPITATES OF Zr-Sn-Nb ALLOY DURING AGING

Abstract: Zirconium-based alloys are being used as fuel cladding and structural materials for nuclear reactors since they have a good irradiation stability, corrosion resistance and acceptable mechanical properties in a reactor environment. Recently, more advanced zirconium-based alloys are required for enhanced operating conditions such as an increased burn-up and higher operation temperatures. Therefore, the development of advanced zirconium alloys for a fuel cladding is being progressed in various countries. Among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…As a result, particles grow with the total annealing time increasing accordingly. Studies show that the precipitation behavior of SPPs is influenced seriously by the final cold rolling reduction before final annealing treatment in zirconium alloys [18][19][20][21] . In the present investigation, the final rolling reduction is 82%, 65%, and 53%.…”
Section: Effect Of Cold Rolling Steps On Spps Precipitation Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, particles grow with the total annealing time increasing accordingly. Studies show that the precipitation behavior of SPPs is influenced seriously by the final cold rolling reduction before final annealing treatment in zirconium alloys [18][19][20][21] . In the present investigation, the final rolling reduction is 82%, 65%, and 53%.…”
Section: Effect Of Cold Rolling Steps On Spps Precipitation Behaviormentioning
confidence: 99%
“…It can be known from Fig.1 and Table. 1 that the alloy intermediate annealed at 640 °C was cold rolled for twice, and the other one final annealed at 640 °C was cold rolled for only once. Study has demonstrated by Chai et al that the pre-deformation before annealing is more effective than prolonging the annealing time in accelerating the phase precipitation [18] . So it may be the main reason that the amount of β-Zr intermediate annealed at 640 °C is larger than that of the alloy finally annealed at 640 °C.…”
Section: Effect Of Final Annealing Processes On Spps Precipitationmentioning
confidence: 99%